2005
DOI: 10.1021/ol051109k
|View full text |Cite
|
Sign up to set email alerts
|

Surprises in the Design of Anion Receptors:  Calorimetry Prevents False Reasoning

Abstract: Supplementing bicyclic guanidinium anion receptors with four sec-carboxamido groups leads to enhanced affinity for oxoanions, however, for a different reason than originally planned. Calorimetric analysis reveals that better binding is due to higher association entropies rather than more negative enthalpies. Thus, molecular design following geometric and functional complementarity principles may misguide supramolecular constructions aimed at a unique host-guest binding mode, as required, e.g., by self-assembly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…259 A strong enthalpic contribution was expected in the case of 167a from the addition of four hydrogen bonding sites. Upon the addition of TBA dihydrogenphosphate to 167a in acetonitrile, ITC studies revealed an initial exothermic 1:1 complexation event followed by an endothermic 1:2 host:guest complexation process.…”
Section: Major Phosphate-binding Functionalitiesmentioning
confidence: 99%
“…259 A strong enthalpic contribution was expected in the case of 167a from the addition of four hydrogen bonding sites. Upon the addition of TBA dihydrogenphosphate to 167a in acetonitrile, ITC studies revealed an initial exothermic 1:1 complexation event followed by an endothermic 1:2 host:guest complexation process.…”
Section: Major Phosphate-binding Functionalitiesmentioning
confidence: 99%
“…Because ITC measures the overall heat change of a solution upon complex formation, it does not enable the effects that result from direct receptor–substrate interactions and from, for example, the desolvation of the binding partners to be distinguished. Information in this regard can sometimes be obtained by using systematic trend analyses that involve changing one parameter, for example, the structure of the receptor, and keeping all the other parameters invariable 20be…”
Section: Resultsmentioning
confidence: 99%
“…Ap lot of the intensity of the CD signal at l = 222 nm versus the Ub content thus indicates the extent of this Ub-dependent conformational change ( Figure 2B,s quares). [21] The binding constanta nd DH8 value extracted from the titrations by assuming a1 :1 binding model were K d = 8.6 10 À5 m and 3.2 kJ mol À1 .B ecause we are at the lower concentration limit [22] suggested for reliable estimates of the thermodynamic parameters, these values were also double-checked by treating the data with different software. [18] ITC of Ub/NGF 1-14 interactions in the presence of Cu II ions CD experiments give indications of the effect of Ub on conformationalc hanges induced on NGF 1-14 ,a sw ell as on the influence of Cu II ions on these conformational changes.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately,n either the sequence of eventsn or the stoichiometry of the step(s) preceding the formation of the NGF 1-14 /Ub speciesc ould be probed by inverting the titrant (i.e.,b ya dding Ub to NGF 1-14 ), as performed in similarc ases, due to limited solubility of Ub. [21] The binding constanta nd DH8 value extracted from the titrations by assuming a1 :1 binding model were K d = 8.6 10 À5 m and 3.2 kJ mol À1 .B ecause we are at the lower concentration limit [22] suggested for reliable estimates of the thermodynamic parameters, these values were also double-checked by treating the data with different software. [23] On the other hand, we could not use concentrations that differed significantly from those indicated above due to solubility problemsa nd the magnitude of the signal detected.…”
Section: Resultsmentioning
confidence: 99%